KAJIAN PEMBUATAN BRIKET ARANG DARI LIMBAH TEMPURUNG PALA ( Myristica fragrans Haitt ) - Erick Manialup; Freeke Pangkerego; Daniel Ludong; Herry F. Pinatik (COCOS, 2015)
ABSTRACT   Charcoal briquettes is solid alternative fuel for oil. This research aimed to evaluate charcoal product from three types of carbonization kiln that used nutmeg shell waste and examine the process of making charcoal briquettes from nutmeg shell waste. The observed characteristics of charcoal briquettes from nutmeg shell waste were  calories value, ash content, and water content. The benefit of this research was producing alternative fuels from renewable agricultural waste into economically valuable products as wells as reducing environmental pollution. This product was charcoal briquettes that could be used for household requirement, small food and beverage industry and canteen.  Key Words: Charcoal Briquet, Nutmeg shell, Carbonization kiln